A comparison of the heart rate deflection point by the S.Dmax method and the ventilatory threshold in sedentary men - Mehdi esbarzadeh; Marefat siahkouhian; Lotfali bolboli (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The aim of this study was to survey of the relationship between heart rate deflection point (HRDP)by the short distance maximum (S.Dmax) and second ventilatory threshold (VT2).Methods: Twenty-one sedentary men volunteers (mean age 19.9±1.31 years; height 173.4±5.3 cm; weight67.9±8.9 kg; maximum oxygen uptake 3.08±0.52 L.min-1) performed an incremental treadmill exercise test toexhaustion. To determine the HRDP, each subject heart rate was recorded by using a polar monitor andanalyzed by a designed computer program. Respiratory gases during the exercise test was measured with agas analyzing system. Data were analyzed using depended t-test, Bland and Altman plots and intraclasscorrelation coefficient.Results: The HRDP was noticed in all subjects. No significant difference (p > 0.05) between the heart rate, oxygenuptake, ventilation, tidal volume and respiratory rate corresponding to HRDP and VT2. Also, results of ICC andBland-Altman plots showed a good agreement between HR and VO2 measured at the HRDP and VT2.Conclusions: It could be concluded that S.Dmax method is an accurate and reliable alternative to the expensiveand time-consuming invasive methods. Therefore, the S.Dmax method can be used for the determination ofanaerobic threshold in healthy young men.